Vietnam trade unions participate in creating harmonious, stable and progressive labor relations at enterprises - Dang X. G. (Human and society, 2017)
keywords: trade unions, harmony, stability, progressiveness, labor relations.
Keywords: стабильность; гармоничность; трудовые отношения; профсоюзы; прогрессивность